Emotion Regulation in Enhancing Adolescents’ Academic Performance - Yuliana Yuliana (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
Adolescence is a transition period between children and adult. There are many changes in physical, sexual, cognitive, and emotion. Aside from coping with those changes, they have to handle their academic performance very well. In order to tackle with those challenges, they need a lot of support from parents, teachers, and peers to prevent maladaptive adolescent behavior and psychopathology. Brain involvement in emotion and learning are amygdala, hippocampus, prefrontal cortex, limbic system, and insula. Emotion regulation is very important in enhancing adolescent academic performance. Emotional competence is the key for success in life.